Restorative rehabilitation of a patient with generalized non-carious cervical lesions : case report = Rehabilitación restaurativa de un paciente con lesiones cervicales no-cariosas generalizadas : reporte de un caso - Zúñiga Castañeda, Roberto
Non-Carious Cervical Lesions (NCCL) are a current problem of multifactorial origin that is associated with the loss of vertical occlusal dimension, hypersensitivity, loss of teeth, fractures, and many other pathologies that affect the masticatory function of the oral cavity. Identification of the etiological factors of NCCL comprises a key piece for the solution of the problem. Based on clinical scientific evidence related with the diagnosis, a restorative treatment must be planned according to the loss of dental structure in order to return function and aesthetics. The purpose of this case report was to describe a 54-year-old male patient who was diagnosed with generalized NCCL combined with occlusal vertical dimension loss. The protocol of the treatment process is described.